Educational strategies in latin america 2020-2023. Metasynthesis - Bustamante-Cabrera, Gladys Inés (2024)
The improvisation of educational strategies in some university centers during the pandemic highlighted the difficulties of teachers and students to adapt to distance learning.  The objective of the study was to know if the teaching methodologies and teaching strategies applied during the pandemic were adequately applied and which methods or educational strategies had a positive impact on university education in Latin America.  To this end, articles were reviewed in five databases, using Boolean operators with descriptors related to the topic.  The research was conducted based on grounded theory, following the PRISMA methodology, using 31 of 1710 articles for categorical analysis in Atlas ti v.22 software. The results revealed seven emerging categories as determinants in the application of educational strategies and that e-learning was the model with the greatest impact and use in Latin American higher education, whose application should be organized as a planned strategy prior to the educational process, also introducing virtual education progressively, associated with permanent teacher and student training for the use of learning tools in the teaching-learning process. Institutions should develop their own applications and materials to reduce distraction and the achievement of planned competencies.